Ag-decorated polymer chip for the determination of the respective concentrations of TTD and Hg2+ by surface-enhanced raman scattering. Issue 4 (18th January 2022) - Yang, Bo; Wang, Ye; Jin, Sila; Guo, Shuang; Park, Eungyeong; Shin, Jin Y.; Zhang, Weiyu; Jung, Young Mee
Abstract : A "hotspot"-rich Ag-nanoparticle-decorated three-dimensional polymer substrate was fabricated, exhibiting an excellent surface-enhanced Raman scattering (SERS) activity. Abstract : A "hotspot"-rich Ag-nanoparticle-decorated three-dimensional polymer substrate was fabricated, exhibiting an excellent surface-enhanced Raman scattering (SERS) activity. 4-Mercaptobenzoic acid (MBA) was selected as a probe molecule for comparing the SERS activity on selected substrates. The proposed detection chip with the adsorption of tetramethylthiuram disulfide (TTD) shows an excellent sensitivity for the quantitative determination of TTD and mercury ions (Hg 2+ ). This chip exhibited a high sensitivity for the trace detection of the targets. Interestingly, we found that the adsorbed TTD is selectively sensitive to Hg 2+ . The SERS band had a significant frequency shift of 11 cm −1 as the concentration of Hg 2+ increased from 10 −10 to 10 −3 mol L −1 . More importantly, the frequency shift of the SERS band exhibited an excellent linear relationship with the concentration of Hg 2+, and the determination limit for Hg 2+ was 10 −10 mol L −1 . Furthermore, the proposed detection chip shows great application potential for the determination of pesticides and Hg 2+ .